В метре друг от друга: [роман] / Рейчел Липпинкотт, Микки Дотри, Тобиас Иаконис - Липпинкотт Рейчел (Young Adult, 2022)
Экземпляры: ф.19 (2022) / Инвентарный номер: 58473 / Цена: / Сис.шифр: 84(7Сое) / Авт.знак: Л 616 / ГРНТИ: 17.82 / ББК: Ш6(7Сое)